Determinan Financing to Deposit Ratio Bank Umum Syariah di Indonesia Periode 2012-2015 - Didit Prakoso; Achsania Hendratmi (Universitas Airlangga, 2017)
The research aimed to know the influence of Capital Adequacy Ratio (CAR), Return on Assets (ROA) and Size of the Financing to Deposit Ratio (FDR) Islamic Banks in Indonesia by using 11 Islamic Banks registered at Bank Indonesia the period 2012 to 2015 as samples. The research used a quantitative approach method. The analysis technique used multiple linearregression analysis and the equation is Y = 0,330 + 1,294(CAR) – 5,931(ROA) + 0,028 (Size). Based on the result of t-test (partial), CAR, ROA and Size significantly affects of FDR with the results of each 6,727, -2,831, 2,564. While the results of f-test (simultant) showed that CAR, ROA and Size significant effect on of FDR with a significance value 0.000. the coefficient of determination shows the value of R-Square (R2) of 54.0%. while the remains of 46% wasexplained by other variables outside the model.